2019
DOI: 10.1093/ofid/ofz359.082
|View full text |Cite
|
Sign up to set email alerts
|

980. Effects of Integrase Strand-Transfer Inhibitor Use on Lipids, Glycemic Control, and Insulin Resistance in the Women’s Interagency HIV Study (WIHS)

Abstract: BackgroundIntegrase strand transfer inhibitor (INSTI)-based antiretroviral therapy (ART) is recommended first-line HIV treatment. We recently demonstrated increased weight gain associated with INSTI use among women living with HIV (WLH) enrolled in the Women’s Interagency HIV Study (WIHS), raising concern for cardiometabolic consequences. We, therefore, evaluated the effects of INSTI use on lipids, insulin resistance, and glycemic control in WLH.MethodsData from 2008 to 2017 were analyzed from WLH enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…In addition, this study revealed that there were statistically insignificant differences in the mean values of LDL-C and median values of TG between two groups. This is supported by the result of the previous study [ 39 ]. Furthermore, a statistically insignificant difference between the two groups was also observed in the median TC/HDL-C ratios.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, this study revealed that there were statistically insignificant differences in the mean values of LDL-C and median values of TG between two groups. This is supported by the result of the previous study [ 39 ]. Furthermore, a statistically insignificant difference between the two groups was also observed in the median TC/HDL-C ratios.…”
Section: Discussionsupporting
confidence: 91%
“…The only metabolic effect observed in our cohort other than weight gain was an increase in glucose levels following a switch from NNRTIs or PIs to INSTI, solely in the subgroup of African descendant males. Similarly to others [ 30 ], we did not identify a worsening of other metabolic parameters such as hypertension or dyslipidemia, following the treatment switch.…”
Section: Discussionsupporting
confidence: 80%
“…Emerging evidence links weight gain with INSTIs and T2DM. When switching to INSTIs, HbA1c has been found to be raised in the INSTI group vs. the non-INSTI group [44,45]. In another cohort study, participants initiating INSTIs (in particular raltegravir) were more likely to develop T2DM compared with NNRTIs [46].…”
Section: Discussionmentioning
confidence: 99%